2016
DOI: 10.7150/ijms.14476
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Subclinical Femoral Vascular Complications after Deployment of two Different Vascular Closure Devices or Manual Compression in the Setting of Coronary Intervention

Abstract: Background: In the past two decades vascular closure devices (VCD) have been increasingly utilized as an alternative to manual compression after percutaneous femoral artery access. However, there is a lack of data confirming a significant reduction of vascular complication in a routine interventional setting. Systematic assessment of puncture sites with ultrasound was hardly performed.Methods: 620 consecutive patients undergoing elective or urgent percutaneous coronary intervention were randomly allocated to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…However, the intravascular VCD was significantly associated with a higher rate of surgical repair due to distal embolization of either the anchor footplate alone or in combination with thrombus compared to extravascular VCD (0.7% for AngioSeal™, 0.2% for StarClose SE®, p < 0.05). Yeni et al, however, found no significant differences of vascular and bleeding complications between intravascular and extravascular devices after PCI 32. Interestingly, a recent comparison of AngioSeal™ and StarClose SE® in non-cardiological procedures revealed also no statistically significant difference between both groups in terms of bleedings and time to hemostasis 33.…”
Section: Discussionmentioning
confidence: 96%
“…However, the intravascular VCD was significantly associated with a higher rate of surgical repair due to distal embolization of either the anchor footplate alone or in combination with thrombus compared to extravascular VCD (0.7% for AngioSeal™, 0.2% for StarClose SE®, p < 0.05). Yeni et al, however, found no significant differences of vascular and bleeding complications between intravascular and extravascular devices after PCI 32. Interestingly, a recent comparison of AngioSeal™ and StarClose SE® in non-cardiological procedures revealed also no statistically significant difference between both groups in terms of bleedings and time to hemostasis 33.…”
Section: Discussionmentioning
confidence: 96%
“…Another evidence of the hemostasis efficacy of VCDs is the reduction of TTA, which directly determines patient satisfaction. After successful hemostasis, conventional MC requires patients to remain on bed rest for 6-12 hours depending on the operation type [ 39 , 50 , 56 ]. According to previous studies, back pain, inconvenient diet, dysuria, and difficult defecation were the main causes of patient discomfort during this long period [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Closure devices themselves can also cause complications such as pseudoaneurysms and larger hematomas. 20,21 However, off-label use of a closure device after such procedures has been previously reported. 22,23 As already reported by Nii et al 4 and Doffer et al, 5 the percutaneous carotid approach is uncertain in hemostasis because the puncture site cannot be seen under direct vision as compared to DCEA.…”
Section: Discussionmentioning
confidence: 99%